Pengaruh Pelatihan Dan Pengembangan Sumber Daya Manusia Terhadap Kinerja Karyawan PT. PLN (Persero) Unit PelaksanaPelayananPelanggan Banjarmasin - Tri Suwarno; Basuki Basuki; Muhammad Harlie; Eddy Mahfudz (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2020)
The purpose of this study was to examine and analyze the effect of training and HR development on the performance of employees of PT PLN (Persero) UP3 Banjarmasin. The research method used is explanatory research with a quantitative approach, where variables are measured using a Likert scale and data collection methods are observation, questionnaires and interviews. The sample in this study were 43 employees of PT PLN (Persero) UP3 Banjarmasin from a total population of 75 people. Data processing in this study using SPSS software version 25, with descriptive analysis and multiple regression analysis hypothesis testing.            The results showed that: (1) Partially, the training variable had a positive and significant effect on the performance of the employees of PT PLN (Persero) UP3 Banjarmasin as evidenced by the tcount of 2.202. (2) Partially, the HR development variable has a significant effect on the performance of the employees of PT PLN (Persero) UP3 Banjarmasin, as evidenced by the tcount value of 2,534. (3) Simultaneously, the variables of training and human resource development have a significant effect on the performance of employees of PT PLN (Persero) UP3 Banjarmasin as evidenced by the value of Fcount = 39,164.